Social enterprises as place of work for people with disabilities – evidence from Poland - Frączkiewicz-Wronka, A.; Wronka-Pośpiech, M.; Porc, R. (Видавництво Львівської політехніки, 2019)
Concern about people with disabilities is now becoming one of the areas of interest within the European Union, which is seeking a cost-effective and socially acceptable solutions aimed at supporting a worthy life of this group of society. Specific areas of action aimed at improving conditions for social inclusion, well-being and the full exercise of the rights of people with disabilities are set out in the “European Disability Strategy 2010–2020: A renewed commitment to a Barrier-Free Europe” (European Disability Strategy 2010–2020: COM (2010) 636). Employment is one of those areas. In order to cope with the professional activation of people with disabilities the pattern of change should start from the immediate environment and living space of disabled. Increasing the number of employment opportunities (e.g. in the form of homework), create and ease the options for self-employment (e.g. social cooperatives). Therefore, the aim of this article is to look at how social enterprises act as labour market entities and what are results of their activity in Poland. We try to prove that social enterprises, i.e. social cooperatives are important entity for the activation of people with disabilities in the labour market by providing the analysis of the activities of two subjects.
Keywords: public management; social enterprise; European Disability Strategy; professional activation; disability; 005.9